Of Exile in America: The Immigrant Experience in “American Land” (2006) and “The Ghost of Tom Joad” (1995) by Bruce Springsteen - Khaled Chouana (Transatlantica)
The aim of this paper is to explore the experience of exile in two folk ballads by Bruce Springsteen, “American Land” (2006) and “The Ghost of Tom Joad” (1995). The paper examines the aesthetic and poetic aspects of the two ballads. “American Land” tells the story of a new immigrant who settles in America and portrays it as a Promised Land. In “The Ghost of Tom Joad,” Springsteen suggests that ordinary people undergo a metaphorical exile that has led John Steinbeck’s protagonist Tom Joad in The Grapes of Wrath (1939) to express his anger against the injustice of the Great Depression.